GENETIC MARKERS AND GENOME-WIDE ASSOCIATION STUDY IN PLANTS - Tussipkan, D.; Pan, Zhaoe (Eurasian Journal of Applied Biotechnology, 2023)
Due to the advanced sequencing technologies, breeders and researchers can use DNA markers to characterize various plants' genetic diversity, kinship, and population structures. This review describes four kinds of genetic markers. Among them, DNA-based molecular markers were discussed in types, basic mechanisms, advantages, and disadvantages in detail. Secondly, we summarize the whole process of a genome-wide association study, and its advantages and disadvantages. We hope that this review provides fundamental information that will be useful for understanding different markers, especially, DNA-based molecular markers, and genome-wide association studies.